2016
DOI: 10.1016/j.gde.2016.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Diverse regulatory interactions of long noncoding RNAs

Abstract: Long noncoding RNAs (lncRNAs) are emerging as important regulators of diverse biological functions. Studies in the past decade indicate that a large number of lncRNAs are enriched in the nucleus and originate from transcriptionally active regulatory elements. These lncRNAs associate with transcription factors and chromatin regulatory elements to fine-tune the transcriptional output of protein coding genes. Importantly, lncRNAs display exquisite tissue specificity in their expression. Understanding how lncRNAs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 80 publications
0
28
0
Order By: Relevance
“…Studies of long non-coding (lnc)RNAs (lncRNAs) such as X inactive specific transcript (Xist), Kcnq1 opposite strand/antisense transcript 1 (Kcnq1ot1) and HOX transcript antisense RNA (HOTAIR), which associate with polycomb repressive complex 2 (PRC2) [2][3][4][5] , revealed that such specialized cellular RNAs could directly bind transcription and chromatin regulatory proteins and modulate their recruitment to genes. There is also evidence that other types of ncRNAs, such as those transcribed from enhancers, also contribute to gene regulation, in either their nascent or mature forms [6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…Studies of long non-coding (lnc)RNAs (lncRNAs) such as X inactive specific transcript (Xist), Kcnq1 opposite strand/antisense transcript 1 (Kcnq1ot1) and HOX transcript antisense RNA (HOTAIR), which associate with polycomb repressive complex 2 (PRC2) [2][3][4][5] , revealed that such specialized cellular RNAs could directly bind transcription and chromatin regulatory proteins and modulate their recruitment to genes. There is also evidence that other types of ncRNAs, such as those transcribed from enhancers, also contribute to gene regulation, in either their nascent or mature forms [6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, lncRNAs can also interact with mediator subunits and regulate mediator complex formation [86,87]. One mode of lncRNA action is to trigger the formation of a stable RNA-DNA triplex to control TF binding specificity on promoter regions [88][89][90][91]. In Arabidopsis, COOLAIR, an antisense transcript originating from the 3 end of the floral repressor gene FLC, can reconfigure double-stranded DNA to a RNA-DNA hybrid and a single-stranded DNA (ssDNA) called 'R-loop' [92].…”
Section: Regulation Mechanism Of Lncrnas In Gene Transcriptionmentioning
confidence: 99%
“…LncRNAs are long transcripts that are not translated into proteins and are emerging as important regulators of function in cells . They have also been linked to cancer progression and acquisition of drug resistance in tumor cells .…”
Section: Transfer Of Ev Rna Can Cause Transfer Of Drug Resistancementioning
confidence: 99%